Metabolic Activation and Carcinogenesis of Tobacco-Specific Nitrosamine N’-Nitrosonornicotine (NNN): A Density Function Theory and Molecular Docking Study - Tengjiao Fan (International Journal of Environmental Research and Public Health, 2019)
N’-nitrosonornicotine (NNN) is one of the tobacco-specific nitrosamines (TSNAs) that exists widely in smoke and smokeless tobacco products. NNN can induce tumors in various laboratory animal models and has been identified by International Agency for Research on Cancer (IARC) as a human carcinogen. Metabolic activation of NNN is primarily initiated by cytochrome P450 enzymes (CYP450s) via 2′-hydroxylation or 5′-hydroxylation. Subsequently, the hydroxylating intermediates undergo spontaneous decomposition to generate diazohydroxides, which can be further converted to alkyldiazonium ions, followed by attacking DNA to form various DNA damages, such as pyridyloxobutyl (POB)-DNA adducts and pyridyl-N-pyrrolidinyl (py-py)-DNA adducts. If not repaired correctly, these lesions would lead to tumor formation. In the present study, we performed density functional theory (DFT) computations and molecular docking studies to understand the mechanism of metabolic activation and carcinogenesis of NNN. DFT calculations were performed to explore the 2′- or 5′- hydroxylation reaction of (R)-NNN and (S)-NNN. The results indicated that NNN catalyzed by the ferric porphyrin (Compound I, Cpd I) at the active center of CYP450 included two steps, hydrogen abstraction and rebound reactions. The free energy barriers of the 2′- and 5′-hydroxylation of NNN are 9.82/8.44 kcal/mol (R/S) and 7.99/9.19 kcal/mol (R/S), respectively, suggesting that the 2′-(S) and 5′-(R) pathways have a slight advantage. The free energy barriers of the decomposition occurred at the 2′-position and 5′-position of NNN are 18.04/18.02 kcal/mol (R/S) and 18.33/19.53 kcal/mol (R/S), respectively. Moreover, we calculated the alkylation reactions occurred at ten DNA base sites induced by the 2′-hydroxylation product of NNN, generating the free energy barriers ranging from 0.86 to 4.72 kcal/mol, which indicated that these reactions occurred easily. The docking study showed that (S)-NNN had better affinity with CYP450s than that of (R)-NNN, which was consistent with the experimental results. Overall, the combined results of the DFT calculations and the docking obtained in this study provide an insight into the understanding of the carcinogenesis of NNN and other TSNAs.